Mranʻ mā Nuiṅʻ ṅaṃ Nhacʻ khraṅʻʺ ʼA myuiʺ sa mīʺ Sāsanā pru ʼA saṅʻʺ krīʺ samuiṅʻʺ ʼa kyañʻʺ khyupʻ = History of the Burma Baptist Women's Missionary Society (Puiʺ Ka raṅʻ Kvanʻpharaṅʻʹ ʼA saṅʻʺ Cā pe, 1984)
Includes biographies of the active members of the society.